Brain training and athletic performance in youth athletes - Park, N. A. (Sam Houston State University, 2023)
The purpose of this study was to explore the effects of cognitive training regarding soccer-specific agility performance with the use of an application, BrainHQ. The study involved 48 soccer athletes, aged 10 to 11, at the competitive and advanced levels, who participated in their competitive spring season. All athletes completed pre- and post-assessments of a modified Y change-of-direction test and a soccer-specific agility test and were included in the analysis. The experimental group used the training app two-four days per week for 10-30 minutes per day over the course of four weeks. The participants were coded as compliant or non-compliant, post-hoc, based on the level of compliance on using the BrainHQ app. The control group used a blind app with no intentional cognitive training purposes for the same time frame as the experimental group. The repeated measures MANOVA (groups x time) with the covariate of compliance study revealed main effects of time and further univariate analyses presented interactions for time x group indicating the BrainHQ app may contribute to perceptual-cognitive athletic performance. The BrainHQ app use by the experimental group showed greatest time improvements in key variables that influence in-game performance such as soccer-specific agility times, movement speed, and decision-making times. Based on the results of this study, recommendations for training programs; and future study recommendations are offered.